2019
DOI: 10.1002/ajb2.1339
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomically broad metagenomic survey of 339 species spanning 57 families suggests cystobasidiomycete yeasts are not ubiquitous across all lichens

Abstract: A taxonomically broad metagenomic survey of 339 species spanning 57 families suggests cystobasidiomycete yeasts are not ubiquitous across all lichens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…L a t e r Č e r n a j o v á a n d Š k a l o u d ( 2 0 1 9 ) f o u n d Cystobasidiomycete yeasts in 95% of Cladonia specimens collected across Europe, though they were suggested to be either part of a superficial biofilm or living within the thallus without associating with the cortex itself. In contrast, Lendemer et al (2019) found them in just nine of the 339 species investigated. The question remains of how abundant and specific cystobasidiomycetes are in lichen symbioses, as well as how consistent the mycobiome might be among different lichen-forming fungal species, e.g., do evolutionary constraints of the mycobiont influence the range and composition of associated fungi?…”
Section: Introductionmentioning
confidence: 86%
“…L a t e r Č e r n a j o v á a n d Š k a l o u d ( 2 0 1 9 ) f o u n d Cystobasidiomycete yeasts in 95% of Cladonia specimens collected across Europe, though they were suggested to be either part of a superficial biofilm or living within the thallus without associating with the cortex itself. In contrast, Lendemer et al (2019) found them in just nine of the 339 species investigated. The question remains of how abundant and specific cystobasidiomycetes are in lichen symbioses, as well as how consistent the mycobiome might be among different lichen-forming fungal species, e.g., do evolutionary constraints of the mycobiont influence the range and composition of associated fungi?…”
Section: Introductionmentioning
confidence: 86%
“…The mycobiont-photobiont studies focused exclusively on New Zealand (Buckley et al 2014;Rafat et al 2015) and Antarctica (Park et al 2014(Park et al , 2015. The third major group of accessions (11%) originated from floristic and (meta-)barcoding surveys (Hur et al 2005;Kim et al 2006;Kelly et al 2011;Orock et al 2012;Schoch et al 2012;Šoun et al 2015;Mark et al 2016b;Jaouen et al 2019;Lendemer et al 2019;Marthinsen et al 2019).…”
Section: Metadata Diversitymentioning
confidence: 99%
“…is defined as a shrubby, sorediate taxon with inflated branches constricted at their point of attachment, minute soralia producing isidiomorphs along the terminal branches, but the taxon was described as highly variable both morphologically and in the medullary chemistry (Clerc 2007;Randlane et al 2009;Gerlach et al 2019aGerlach et al , 2020. It has been reported from all major regions and is considered presumably subcosmopolitan (Awasthi 1986;Clerc 1987Clerc , 2004Clerc , 2006Clerc , 2007Clerc , 2011bMarcano et al 1996;Clerc & Herrera-Campos 1997;Halonen et al 1998;Elix & McCarthy 1998Fos & Clerc 2000;Herrera-Campos et al 2001;Galloway 2007;Hinds & Hinds 2007;Randlane et al 2009;Smith et al 2009;Kelly et al 2011;Rodriguez et al 2011a;Saag et al 2011;Ohmura 2012;Schoch et al 2012;Noer et al 2013;Santiago et al 2013;Truong et al 2013a;Millanes et al 2014;Araujo 2016, as Gerlach et al 2019a;Lendemer et al 2019;Lücking et al 2020c). Truong et al (2013a) first demonstrated that U. cornuta s.lat.…”
Section: Usnea Subgenus Neuropogon New Zealand Cladementioning
confidence: 99%
“…The significance of these lichen yeasts was discussed by the late Franz Oberwinkler (2017) who concluded that 'it is obvious that basidiomycetous yeasts in lichen thalli are not a third component of symbiosis, but rather the vegetative propagules of mycoparasites'. Moreover, a broad survey for basidiomycete yeasts through metagenomic analysis of 339 lichen species (of 25 orders) confirmed the yeasts in only 2.7% of the sampled species (Lendemer et al, 2019), although their metagenomic approach may be much less sensitive than PCR assays with specific primers. It remained, therefore, unclear, how ubiquitous and specific these yeast asexual stages actually were.…”
mentioning
confidence: 99%